L’antropologia teologica nella Caritas in veritate di Benedetto XVI - Carrara, Alberto (Alpha Omega, 2014)
Summary: The human being has always held a central place in reflections on faith and, from the beginning, has been the main centre of concern within the pastoral activity of the Church. This fundamental reality emerges from Benedict XVI’s social encyclical, Caritas in veritate, in the context of a grave economic crisis at the global level, marked at the same time by the fact that it is a true and proper “crisis” of humanity, both cultural and moral. In this work, after outlining the historical context within which Benedict XVI’s social encyclical is situated and after presenting its structure and the main matters which it examines, the author offers a synthesis of the theological anthropology which constitutes its ‘red line’, structuring the en-cyclical around the major theological themes of this discipline: the creation of the human being by God and the constitution of our being and of our faculties; the reality of sin and of our recreation in sanctifying grace, and concluding with our final end or destiny, eternal life.